Involuntary nocturnal rituals in the Lycas ship (Petr. Sat. 99-115) - San Vicente, Jose Ignacio (ARYS. Antigüedad: Religiones y Sociedades, 2023)
An episode of the Satyricon relates the shaving of the heads of Encolpius and Giton on board Lycas’ ship in the moonlight. Lycas interpreted the event as a sacrilege associated with the ultimum votum of sailors in the event of a shipwreck. The ritual and the reading made by the ship’s captain are examined, leading to the conclusion that the process is based on the protocol followed in Rome in the case of a prodigy. Until it had been recognized as such by the Senate, it was not considered an extraordinary phenomenon. Lycas’ drowning at sea is attributed to his failure to carry out the purification he had prescribed. His punishment should be attributed to the revenge of the demons associated with the acts of purification, although Neptune was supposed to be the instrument.